Penggunaan Bentuk Sapaan Julukan oleh Masyarakat Desa Rumoong-Lansot - Lumoindong, Boy; Tulung, Golda Juliet; Ranuntu, Christian G. (Universitas Sam Ratulangi, 2017)
Nicknaming and its uses in daily communication by the people of Rumoong-Lansot villages are considered as both social and lingual phenomena that have existed since a very long time ago and unconsciously have become the internal part of daily interaction of the people. A well-maintained relationship among the individuals in the society is one of the major factors that endorsed them to address each other by using proper nicknames. No matter old or young people, male or female, wealthy or destitute, indigenous or non indigenous, are all unexceptional unrestrained for nicknaming and employing nicknames between one another. The results of this research showed that term of nicknames employed by the people of Rumoong-Lansot villages concealed nearly the entire elements of internal linguistics and external linguistics. In term of types, all those nicknames that have been successfully collected and analyzed can be categorized into the following aspects: physical state, home and place of birth, occupation, particular moment, and every other feature that promotes the creation of the nicknames. Generally speaking, every single nickname employed by the people is conditioned to identify one specific member of the society in order to generate a clear and unimpeded sort of communication. Specifically, every single nickname is responsible to provide a distinguished portrayal of any peculiar individual in the society, and even more definite, about his most dominating distinctive characteristics.